Sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density and preparation method thereof

By introducing Li+, La3+, and Zr4+ ions into sodium bismuth titanate-based ceramic materials and employing a rolling process, the problem of insufficient energy storage density and stability of sodium bismuth titanate-based ceramic materials over a wide temperature range has been solved, achieving high energy storage density and excellent temperature and frequency stability, making it suitable for advanced energy storage systems.

CN120903933APending Publication Date: 2025-11-07SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511061041.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing sodium bismuth titanate-based ceramic materials have difficulty achieving both high energy density and good stability over a wide temperature range, especially under complex operating conditions where material stability and energy storage efficiency are hard to balance.

Method used

Using the chemical composition (1-x)(0.85Na0.5Bi0.5TiO3-0.15CaTiO3)-x(Li0.5La0.5)(Zr0.8Ti0.2)O3, Li+, La3+, and Zr4+ ions are introduced through A/B site co-doping to break the long-range ordered crystal structure and induce lattice distortion. Combined with rolling process, ceramic materials are prepared to improve breakdown field strength and energy storage performance.

Benefits of technology

It maintains high energy storage density and efficiency over a wide temperature range, making it suitable for advanced energy storage systems. It also features excellent temperature and frequency stability, high power density, and fast discharge rate, making it suitable for high-power pulse equipment, power generation systems, and new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120903933A_ABST
    Figure CN120903933A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density and a preparation method thereof, the chemical formula is (1-x) (0.85 Na0. 5Bi0. 5TiO3-0. 15CaTiO3)-x (Li0. 5La0. 5) (Zr0. 8Ti0. 2) O3 ((1-x) NTT-CT-xLLZT), and x is more than or equal to 0.05 and less than or equal to 0.20. The invention further discloses a preparation method of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density. The compact ceramic is obtained by regulating and controlling the doping amount of LLZT, the energy storage density at room temperature reaches 5.74 J / cm < 3 >, the efficiency is 85.7%, the current density is 506.9 A / cm < 2 >, the power density is 76.03 MW / cm < 3 > and the discharge time is 64.1 ns under an electric field of 200 kV / cm, the defects that NBT-based ceramic is low in breakdown field strength, small in energy storage density and large in loss are overcome, and the compact ceramic has excellent energy storage performance and good temperature frequency stability and is suitable for wide working range, large power density, fast discharge and high efficiency. The method is expected to be used in advanced energy storage systems.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of dielectric energy storage ceramic capacitors, and particularly relates to a sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density and a preparation method thereof. BACKGROUND

[0002] With the intensification of global energy crisis, the production, conversion and storage technology of clean energy has become a research hotspot. Among many energy storage devices, ceramic dielectric capacitors have shown a broad application prospect in high-power pulse equipment, power generation systems, electromagnetic devices and new energy vehicles due to their simple preparation process, fast charge and discharge rate, good temperature stability and high energy storage efficiency. The key parameters for evaluating the performance of ceramic energy storage materials include maximum polarization strength, residual polarization strength, breakdown field strength, etc., among which the available energy storage density and energy storage efficiency are important indicators for measuring the practical value of the materials. An ideal energy storage material should have high breakdown field strength, large polarization strength difference and low energy loss.

[0003] Among the current mainstream energy storage dielectric materials, relaxor ferroelectric materials have attracted much attention due to their excellent power density, fast charge and discharge response and good temperature stability. (Na 0.5 Bi 0.5 )TiO3 ceramic (NBT) is a kind of ferroelectric ceramic, and is also the most widely used base material of relaxor ferroelectric ceramic. Pure NBT material is a typical ABO3 perovskite structure, and has a high P max It can be used for energy storage, but its P r The large BDS and low BDS of pure NBT make it impossible to be directly applied to energy storage. Therefore, in order to obtain a material with excellent energy storage performance, the pure NBT material is usually modified to reduce P r and improve the breakdown. However, there are still significant deficiencies in maintaining high energy storage density while achieving wide temperature stability, especially in the stability and energy storage efficiency of the material under complex working conditions. SUMMARY

[0004] The purpose of the present application is to overcome the shortcomings of the prior art, and to provide a sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density and a preparation method thereof, so as to solve the problem that the NBT form of ferroelectric ceramic in the prior art cannot simultaneously satisfy wide temperature stability and high energy storage density.

[0005] To achieve the above purpose, the technical scheme adopted by the present application is as follows: A sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density, the chemical formula of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage performance is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein 0.05≤ x ≤0.20.

[0006] The further improvement of the present application is: Preferably, the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage performance has an energy storage density of 3.85~10.08 J / cm 3 , and an energy storage efficiency of 81.2~88 % under the condition of 10 Hz frequency.

[0007] A preparation method of a sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density, comprising the following steps: (1) according to the stoichiometric ratio of (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3((1- x ), uniformly mix Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 to obtain a first raw material powder, and obtain a pre-sintered solid after pre-sintering; (2) ball milling and sieving the pre-sintered solid obtained in step (1) to obtain a second raw material powder; (3) pressing the raw material powder obtained in step (2) into a shape, and then high-temperature sintering to obtain a ceramic material with wide temperature stability and high energy storage performance.

[0008] Preferably, in step (1), the pre-sintering temperature is 800~850 °C, and the pre-sintering is performed for 3~5 hours.

[0009] Preferably, in step (3), the pressing is performed by using a cold isostatic pressing machine.

[0010] Preferably, the cold isostatic pressing forming pressure is 180~220 MP, and the time is 3 min.

[0011] Preferably, in step (3), the sintering temperature is 1060~1120 °C and the sintering time is 2~4 hours.

[0012] Preferably, the process also includes step (4), in which the raw material powder obtained in step (2) is mixed with PVA, rolled and compressed into a sheet with a thickness of 30-50 μm, and then sintered at high temperature after debinding to obtain a ceramic material with wide temperature stability and high energy storage performance.

[0013] Preferably, the glue discharge temperature is 600 °C and the glue discharge time is 24 hours.

[0014] Preferably, the sintering temperature is 1160 °C and the sintering time is 2 hours.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a sodium bismuth titanate-based ceramic material with wide temperature stability and high energy density, the chemical formula of which is: (1- x (0.85Na) 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 (Zr) 0.8 Ti 0.2 )O3((1- x NBT-CT- x LLZT), where 0.05≤ x ≤0.20, the ceramic material selected is relaxor ferroelectric 0.85Na 0.5 Bi 0.5 Using TiO3-0.15CaTiO3(0.85NBT-0.15CT) ceramic as the matrix material, Li was incorporated through A / B site co-doping. + La 3+ Zr 4+ Plasma is introduced into the crystal lattice, thereby disrupting the long-range ordered crystal structure of the matrix and inducing lattice distortion to achieve relaxation. In a 0.85NBT-0.15CT matrix, Li is introduced... + Li + With its small ionic radius, the introduction of Li into ceramics results in less lattice distortion. The introduction of Li can lower the sintering temperature, reducing the volatilization of Bi and Na and increasing ceramic density. During sintering, an appropriate amount of Li can form a liquid phase, which promotes homogeneity and densification, reduces grain size, and increases the breakdown field strength. The addition of the lanthanide element La can effectively reduce… P r and coercive electric field ( Ec This reduces leakage current density and improves the sample's BDS and η Through research (Li 0.5 La 0.5 (Zr) 0.8 Ti 0.2 The effects of O3 content on the structure, energy storage performance, dielectric properties, and temperature stability of the 0.85NBT-0.15CT matrix were investigated to prepare ceramic materials with wide temperature stability and high energy storage density. The energy storage performance was further improved by rolling process. The sample prepared by rolling process after adding PVA has a larger density, better compactness, smaller thickness, and the grain size will be further reduced on the basis of solid-state method. The breakdown field strength is greatly improved, thus obtaining excellent energy storage performance.

[0016] This invention also discloses a method for preparing sodium bismuth titanate-based ceramic materials with wide temperature stability and high energy storage density. The method involves uniformly mixing raw material powders, drying and sieving them, then pressing them into shape, and finally sintering them to obtain sodium bismuth titanate-based ceramic materials with high energy storage performance and ultrafast discharge rate. The preparation process of this invention is simple and easy to implement. The raw materials used do not contain polluting elements such as lead, are environmentally friendly, and are inexpensive, making them suitable for industrial mass production. This preparation method controls (Li...) 0.5 La 0.5 (Zr) 0.8 Ti 0.2 By doping with O3 and sintering at 1060–1120°C, dense sodium bismuth titanate-based ceramics are obtained. A yield of up to 5.74 J / cm³ can be achieved at room temperature. 3 It boasts an energy storage performance of 85.7%, and a current density of 506.9 A / cm² at room temperature and an electric field strength of 200 kV / cm. 2 The power density can reach 76.03 MW / cm³. 3 The discharge time is as short as 64.1 ns. After employing a rolling process, 0.15LLZT-VPP can achieve a discharge rate of up to 10.08 J / cm³ at room temperature. 3 With an energy storage performance of 85%, it effectively overcomes the shortcomings of sodium bismuth titanate-based ceramic dielectric materials, such as low dielectric breakdown field strength, low energy storage density, and high dielectric loss. The prepared sodium bismuth titanate-based energy storage ceramic dielectric material exhibits excellent energy storage performance and good temperature and frequency stability. It is suitable for a wide range of operating temperatures, frequencies, and application fields, and has a large power density and ultrafast discharge rate, making it promising for application in advanced energy storage systems.

[0017] Furthermore, the material of this invention exhibits a slender hysteresis loop with a small loop area at room temperature, resulting in excellent energy storage density and efficiency, with an energy storage density reaching 3.85~10.08 J / cm². 3, the energy storage efficiency reaches 81.2~88 %; and the energy storage density and efficiency of the ceramic material with wide temperature stability in the application have good temperature stability and frequency stability, x when the value of x is 0.15, the energy storage density of the ceramic material under an electric field strength of 150 kV / cm is maintained at 0.756~0.71 J / cm 3 between 20~100 Hz at room temperature, the energy storage density of the ceramic material under an electric field strength of 150 kV / cm is maintained at 0.784~0.72 J / cm 3 between 1~100 Hz at room temperature, the energy storage efficiency is maintained at 90.68~92.22 %. The ceramic material with high energy storage density in the application has good stability in the temperature range of 20~140 DEG C, is suitable for a wider working temperature range and application field, and is expected to be applied in the field of advanced energy storage. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 : XRD patterns of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in all examples.

[0019] Figure 2 : Scanning electron microscope image of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 1 at room temperature.

[0020] Figure 3 : Scanning electron microscope image of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 2 at room temperature.

[0021] Figure 4 : Scanning electron microscope image of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 3 at room temperature.

[0022] Figure 5 : Scanning electron microscope image of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 4 at room temperature.

[0023] Figure 6 : Scanning electron microscope image of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 5 at room temperature.

[0024] Figure 7 : Electric hysteresis loop diagram of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 1 at room temperature (the test frequency is 10 Hz).

[0025] Figure 8 : Electric hysteresis loop diagram of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 2 at room temperature (the test frequency is 10 Hz).

[0026] Figure 9 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 3 at room temperature (test frequency: 10 Hz).

[0027] Figure 10 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 4 at room temperature (test frequency: 10 Hz).

[0028] Figure 11 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 5 at room temperature (test frequency: 10 Hz).

[0029] Figure 12 : The dielectric temperature spectrum of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 1 at different test frequencies.

[0030] Figure 13 : The dielectric temperature spectrum of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 2 at different test frequencies.

[0031] Figure 14 : The dielectric temperature spectrum of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 3 at different test frequencies.

[0032] Figure 15 : The dielectric temperature spectrum of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 4 at different test frequencies.

[0033] Figure 16 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 3 at 150 kV / cm electric field intensity, at 20 °C, 40 °C, 60 °C, 80 °C, 100 °C, 120 °C and 140 °C (test frequency: 10 Hz); Figure 17 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 3 at 150 kV / cm electric field intensity, at 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz and 100 Hz (test temperature: room temperature).

[0034] Figure 18 : The over-damped discharge curve of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density prepared in Example 3 at room temperature and 200 kV / cm electric field intensity; Figure 19: The undamped discharge curve of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density prepared in Example 3 at room temperature and an electric field strength of 200 kV / cm; Figure 20 : The discharge energy density versus time curve of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density prepared in Example 3 at room temperature and an electric field strength of 200 kV / cm.

[0035] Figure 21 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 5 at an electric field strength of 300 kV / cm at 20 °C, 40 °C, 60 °C, 80 °C, 100 °C, 120 °C and 140 °C (test frequency: 10 Hz); Figure 22 : The electric hysteresis loop of the sodium bismuth titanate-based ceramic material with wide temperature stability prepared in Example 5 at an electric field strength of 300 kV / cm at 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz and 100 Hz (test temperature: room temperature). DETAILED DESCRIPTION

[0036] The application will be further described in details below with reference to the accompanying drawings: To enable persons skilled in the art to better understand the features and effects of the present application, the following is a general description and definition of the terms and phrases mentioned in the specification and claims. Unless otherwise specified, all technical and scientific words used herein have the usual meanings understood by those skilled in the art of the present application, and in the event of a conflict, the definitions in the specification shall prevail.

[0037] In this document, unless otherwise specifically stated, "comprise", "comprises", "comprising", "contain", "contains", "containing", "have", "has", "having" or similar words are inclusive and mean "consist essentially of and "consist essentially of", for example, "A comprises a" means "A comprises a and other" and "A comprises only a".

[0038] The present application will be further described in details below with reference to the accompanying drawings:

[0039] The following examples use apparatus and equipment that are conventional in the art. The experimental methods in the following examples, unless otherwise specified, are generally in accordance with conventional conditions, or in accordance with the conditions recommended by the manufacturer. The following examples use various raw materials, unless otherwise specified, all of which are conventional commercially available products, and the specifications thereof are conventional in the art. In the specification of the present application and in the following examples, unless otherwise specified, "%" means weight percent, "parts" means weight parts, and the ratio means weight ratio.

[0040] A sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density is disclosed, which has a chemical formula of: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3((1- x )NBT-CT- x LLZT), wherein 0.05≤ x ≤0.20.

[0041] The sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density has an energy storage density of 3.85~10.08 J / cm 3 and an energy storage efficiency of 81.2~88 % at room temperature and a frequency of 10 Hz; at 10 Hz, 20~140 °C, the ceramic material with wide temperature stability and high energy storage density of Example 3 has an energy storage density of 0.756~0.71 J / cm 3 and an energy storage efficiency of 91.87~92.29 % at an electric field intensity of 150 kV / cm; at room temperature, 1~100 Hz, the ceramic material with wide temperature stability and high energy storage density of Example 3 has an energy storage density of 0.784~0.72 J / cm 3 and an energy storage efficiency of 90.69~92.22 % at an electric field intensity of 150 kV / cm. In addition, the ceramic material with wide temperature stability and high energy storage density of Example 3 has a current density of 506.9 A / cm 2 , a power density of 76.03 MW / cm 3 , and a discharge time of 64.1 ns at room temperature and an electric field intensity of 200 kV / cm. At 10 Hz, 20~140 °C, the ceramic material with wide temperature stability and high energy storage density of Example 5 has an energy storage density of 1.94~1.76 J / cm 3The energy storage efficiency is maintained between 89.5~90.5 %; under the room temperature, 1~100 Hz, the ceramic material with wide temperature stability and high energy storage density of example 5 maintains the energy storage density of 1.97~1.87 J / cm 3 The energy storage efficiency is maintained between 86.96~89.70 %.

[0042] The preparation method of the sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage performance comprises the following steps: (1) according to the chemical formula: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, the analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are compounded, wherein x represents the mole fraction, and 0.05≤ x ≤0.20, the anhydrous ethanol is used as the medium, the uniform mixing is carried out through the ball milling for 22~24 hours, then the drying is carried out at 80 °C, the 120 mesh sieve is passed, the briquetting is carried out, and then the pre-sintering is carried out at 800~850 °C for 3~5 hours, so as to obtain the block solid, then the block solid is crushed and passed through the 120 mesh sieve, so as to obtain the pre-sintered powder; (2) the pre-sintered powder obtained in the step (1) is ball milled for 22~24 hours with the anhydrous ethanol as the medium, then the drying is carried out at 80 °C, and the raw material powder is obtained after the 120 mesh sieve is passed; (3) the raw material powder obtained in the step (2) is cold isostatic pressed, wherein the pressure of the cold isostatic pressing is 180~220 MPa, and the pressure maintaining time is 3 minutes; the circular sheet is pressed after the pressure is added, and then the porcelain is sintered by maintaining the temperature at 1060~1120 °C for 2~4 hours, so as to obtain the ceramic material with wide temperature stability and high energy storage density; (4) the ceramic material with wide temperature stability and high energy storage density prepared is tested by X-ray diffraction; (5) the ceramic material with wide temperature stability and high energy storage density prepared is tested by field emission scanning electron microscope; (6) the sintered sample is processed into a thin sheet with smooth two surfaces and a thickness of about 0.1 mm, gold-plated electrodes are added, then the ferroelectric performance is tested at different temperatures and frequencies, and the energy storage characteristics are calculated, so as to obtain the recoverable energy storage density (Pr) W rec ), the total energy storage density (Wtot) Wtotal ) and energy storage efficiency ( η ) ; (7) The sintered sample is processed into a thin sheet with smooth surfaces and a thickness of about 0.3 mm, silver electrode is plated, and then the charge and discharge performance is tested at room temperature and an electric field strength of 120 kV / cm, and the discharge characteristics are calculated, the current density ( C D ), power density ( P D ) and discharge energy density ( W dis ) are calculated by the following formulas: (4) (5) (6) wherein, C D and P D respectively represent the current density and the power density, I max represents the maximum current, E represents the electric field strength, S represents the electrode area, R represents the load resistance, V represents the sample volume.

[0043] In a further embodiment.

[0044] (8) The raw material powder obtained in step (2) is mixed with PVA and compressed into a thin sheet with a thickness of 30-50 μm by roller milling. Through this step, the thickness of the sample obtained by adding PVA and roller milling is smaller than that obtained by the solid phase method, the density is greater, and the grain size is smaller, so that the performance of the final product is better.

[0045] (9) The 30-50 μm thin sheet is degassed at 600 °C for 24 hours.

[0046] (10) After degassing, high-temperature sintering is carried out to obtain a ceramic material with wide temperature stability and high energy storage performance, the sintering temperature is 1160 °C, and the sintering time is 2 hours.

[0047] The content of the present application can be further understood by the following examples given, but it is not a limitation of the present application.

[0048] Example 1 The chemical formula of the sodium bismuth titanate-based ceramic material in this example is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein x represents the molar fraction, and x = 0.05. The preparation method of the above-mentioned sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) according to the chemical formula: 0.95(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-0.05(Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are mixed uniformly by ball milling for 24 hours in anhydrous ethanol medium, and then dried at 80 °C, sieved through a 120 mesh sieve, briquetted, and then pre-fired at 850 °C for 4 hours to obtain a block solid, and then the block solid is crushed and sieved through a 120 mesh sieve to obtain a pre-fired powder; (2) the pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol medium for 24 hours, and then dried at 80 °C, sieved through a 120 mesh sieve to obtain a raw material powder; (3) the raw material powder obtained in step (2) is cold isostatic pressed, wherein the pressure of the cold isostatic pressing is 200 MPa, and the pressure holding time is 3 minutes; the round sheet is pressed and sintered into a ceramic at 1100 °C for 4 hours to obtain the ceramic material with wide temperature stability and high energy storage density.

[0049] The prepared sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density is tested by X-ray diffraction, as shown in Figure 1 , it can be seen from the XRD pattern that the ceramic material obtained in this embodiment has a pure perovskite structure and high crystallinity. The surface grain growth of the sintered ceramic sample is tested by field emission scanning electron microscopy, as shown in Figure 2 . The sintered sample is processed into a thin sheet with smooth two surfaces and a thickness of about 0.1 mm, gold-plated electrodes are used, and then the ferroelectric properties thereof are tested at room temperature and a frequency of 10 Hz, as shown in Figure 7 . The hysteresis loop of the ceramic material in this embodiment measured at room temperature is shown, and the energy storage characteristics are calculated from the hysteresis loop, and the energy storage density of the energy storage ceramic in this embodiment at room temperature can reach 3.85 J / cm 3 , and the energy storage efficiency can reach 81.2 %. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1. The dielectric temperature spectrum of the energy storage ceramic material at different test frequencies is shown inFigure 12 As shown, the Curie temperature at 1 MHz is 26.99 °C, and the maximum dielectric constant is 835.5.

[0050] Example 2 The chemical formula of the sodium bismuth titanate-based ceramic material of this example is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein x represents the mole fraction, and x = 0.10. The method for preparing the sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) According to the chemical formula: 0.90(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-0.10(Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are weighed and mixed uniformly in anhydrous ethanol by ball milling for 24 hours, and then dried at 80 °C, sieved through a 120-mesh sieve, pressed into a block, and then pre-fired at 840 °C for 3 hours to obtain a block-shaped solid, which is then crushed and sieved through a 120-mesh sieve to obtain a pre-fired powder; (2) The pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol for 24 hours, and then dried at 80 °C, sieved through a 120-mesh sieve to obtain a raw material powder; (3) The raw material powder obtained in step (2) is cold isostatic pressed, wherein the pressure is 200 MPa and the pressure holding time is 3 minutes; the circular sheet is pressed and sintered into a ceramic at 1070 °C for 4 hours to obtain the ceramic material with wide temperature stability and high energy storage density.

[0051] The prepared sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density is subjected to X-ray diffraction test, as shown in Figure 1 As can be seen from the XRD pattern, the ceramic material obtained in this example is mainly in perovskite structure, and has high crystallinity, and the second phase is ZrO2. Field emission scanning electron microscopy is used to test the surface grain growth of the sintered ceramic sample, as shown in Figure 3The second phase is ZrO2. The sintered sample is processed into a thin slice with smooth surface and thickness of about 0.1 mm, gold-plated electrode, and then tested for ferroelectric properties at room temperature and frequency of 10 Hz, as shown in Figure 8 The hysteresis loop of the ceramic material of the present embodiment measured at room temperature is shown. The energy storage density of the energy storage ceramic of the present embodiment at room temperature can reach 5.04 J / cm 3 , and the energy storage efficiency can reach 84.8 %. The energy storage properties of the energy storage ceramic material of the present embodiment at room temperature are shown in Table 1. The dielectric temperature spectrum of the energy storage ceramic material at different test frequencies is shown in Figure 13 , the Curie temperature at 1 MHz is 63.94 °C, and the maximum dielectric constant is 700.5.

[0052] Example 3 The chemical formula of the sodium bismuth titanate-based ceramic material of the present embodiment is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein x represents the mole fraction, and x =0.15. The preparation method of the sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) According to the chemical formula: 0.85(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-0.15(Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are mixed uniformly by ball milling for 24 hours in anhydrous ethanol medium, and then dried at 80 °C, sieved through 120 mesh, pressed into a block, and then pre-fired at 850 °C for 4 hours to obtain a block solid. The block solid is then crushed and sieved through 120 mesh to obtain a pre-fired powder; (2) The pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol medium for 24 hours, then dried at 80 °C, sieved through 120 mesh, and then the raw material powder is obtained; (3) The raw material powder obtained in step (2) is subjected to cold isostatic pressing, wherein the pressure of cold isostatic pressing is 200 MPa and the holding time is 3 minutes; after being pressed into a disc, it is sintered into a ceramic at 1140 °C for 4 hours to obtain the ceramic material with wide temperature stability and high energy density.

[0053] The prepared sodium bismuth titanate-based ceramic material, exhibiting wide temperature stability and high energy density, was subjected to X-ray diffraction testing, such as... Figure 1 The XRD pattern shows that the ceramic material obtained in this embodiment is mainly composed of perovskite structure with high crystallinity, and the second phase is ZrO2. Field emission scanning electron microscopy was used to test the surface grain growth of the sintered ceramic sample. Figure 4 The second phase shown is ZrO2. The sintered sample was processed into a smooth sheet with a thickness of approximately 0.1 mm, plated with gold electrodes, and then its ferroelectric properties were tested at room temperature and a frequency of 10 Hz. Figure 9 The figure shows the hysteresis loop of the ceramic material in this embodiment measured at room temperature. Based on the energy storage characteristics calculated from the hysteresis loop, the energy storage density of the energy storage ceramic in this embodiment can reach 5.74 J / cm³ at room temperature. 3 The energy storage efficiency can reach 85.7%. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1. The dielectric temperature spectrum of this energy storage ceramic material at different test frequencies is shown below. Figure 14 As shown, the Curie temperature at 1 MHz is 74.7 °C, and the maximum dielectric constant is 586.4.

[0054] like Figure 16 The figure shows the hysteresis loops of the energy storage ceramic material in this embodiment at 20 °C, 40 °C, 60 °C, 80 °C, 100 °C, 120 °C, and 140 °C under an electric field strength of 150 kV / cm at a frequency of 10 Hz. Energy storage characteristics are calculated from the hysteresis loops, showing that the energy storage ceramic material in this embodiment maintains an energy density of 0.756–0.71 J / cm³ at a frequency of 10 Hz within a temperature range of 20–140 °C. 3 Between these values, the energy storage efficiency remained between 91.87% and 91.29%. For example... Figure 17 The figure shows the hysteresis loops of the energy storage ceramic material in this embodiment at frequencies of 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz, and 100 Hz under room temperature and an electric field strength of 150 kV / cm. Energy storage characteristics calculations based on the hysteresis loops show that the energy storage density of the energy storage ceramic material in this embodiment remains between 0.784 and 0.72 J / cm² under room temperature and an electric field strength of 150 kV / cm. 3The energy storage efficiency remained between 90.69% and 92.22%, indicating that the energy storage ceramic material of this embodiment has high energy storage performance and exhibits good temperature and frequency stability. Table 1 shows the energy storage characteristics of the energy storage ceramic material at room temperature. Table 2 shows the energy storage characteristics of the energy storage ceramic material of this embodiment at 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, and 140°C under a frequency of 10 Hz and an electric field strength of 150 kV / cm. Table 3 shows the energy storage characteristics of the energy storage ceramic material of this embodiment at 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz, and 100 Hz under a room temperature and an electric field strength of 150 kV / cm.

[0055] The sintered sample was processed into a smooth sheet with a thickness of approximately 80 μm, coated with gold electrodes, and then its charge-discharge performance was tested at room temperature and an electric field strength of 200 kV / cm. Figure 18 The figure shows the overdamped discharge curve of the ceramic material in this embodiment, measured at room temperature and an electric field strength of 200 kV / cm. Figure 19 The figure shows the underdamped discharge curve of the ceramic material in this embodiment measured at room temperature and an electric field strength of 200 kV / cm. Calculations based on the charge-discharge characteristics of the underdamped discharge show that the current density of the energy storage ceramic in this embodiment can reach 506.9 A / cm² at room temperature and an electric field strength of 200 kV / cm. 2 The power density can reach 76.03 MW / cm³. 3 .like Figure 20 The figure shows the discharge energy density versus time curve calculated from the overdamped discharge curves of the ceramic material in this embodiment measured at room temperature and an electric field strength of 200 kV / cm. Calculations of the charge-discharge characteristics show that the discharge energy density of the energy storage ceramic in this embodiment can reach 0.85 J / cm² at room temperature and an electric field strength of 200 kV / cm. 3 The discharge time is as short as 64.1 ns. Table 4 shows the charge-discharge characteristics of the ceramic material with wide temperature stability and high energy density in Example 3 at room temperature and an electric field strength of 200 kV / cm.

[0056] Example 4 The chemical formula of the sodium bismuth titanate-based ceramic material in this example is: (1- x (0.85Na) 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 (Zr) 0.8 Ti 0.2 O3, of which xexpressing the molar fraction, and x =0.20. The preparation method of the above-mentioned sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) according to the chemical formula: 0.80 (0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-0.20(Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are mixed uniformly by ball milling for 24 hours in anhydrous ethanol medium, and then dried at 80 °C, sieved through a 120-mesh sieve, briquetted, and then pre-fired at 850 °C for 4 hours to obtain a block solid, which is then crushed and sieved through a 120-mesh sieve to obtain a pre-fired powder; (2) the pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol medium for 24 hours, and then dried at 80 °C, sieved through a 120-mesh sieve to obtain a raw material powder; (3) the raw material powder obtained in step (2) is cold isostatic pressed, wherein the pressure is 220 MPa and the pressure holding time is 3 minutes; the circular sheet is pressed and sintered into a ceramic at 1120 °C for 2 hours to obtain the ceramic material with wide temperature stability and high energy storage density.

[0057] The prepared sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density is subjected to X-ray diffraction test, as shown in Figure 1 , it can be seen from the XRD pattern that the ceramic material obtained in this embodiment is mainly of perovskite structure, has high crystallinity, and the second phase is ZrO2. The surface grain growth of the sintered ceramic sample is tested by field emission scanning electron microscopy, as shown in Figure 5 , the second phase is ZrO2 crystal in spherical structure. The sintered sample is processed into a thin sheet with smooth two surfaces and a thickness of about 0.1 mm, gold-plated electrodes are applied, and then the ferroelectric properties thereof are tested at room temperature and a frequency of 10 Hz, as shown in Figure 10 , the hysteresis loop of the ceramic material in this embodiment measured at room temperature is shown, and the energy storage characteristics are calculated from the hysteresis loop, and the energy storage density of the energy storage ceramic in this embodiment at room temperature can reach 4.3 J / cm 3 , and the energy storage efficiency can reach 88.0 %. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1. The dielectric temperature spectrum of the energy storage ceramic material at different test frequencies is shown in Figure 15 , the Curie temperature at 1 MHz is 57.7 °C, and the maximum dielectric constant is 486.4.

[0058] Example 5 The chemical formula of the sodium bismuth titanate-based ceramic material of this example is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein x represents the mole fraction, and x = 0.15. The above sodium bismuth titanate-based ceramic material with wide temperature stability is prepared by a rolling process, hereinafter referred to as 0.15LLZT-VPP. The preparation method of the above sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) Analytically pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are weighed according to the chemical formula 0.85(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, mixed uniformly in anhydrous ethanol medium by ball milling for 24 hours, then dried at 80 °C, sieved through a 120 mesh sieve, briquetted, and then pre-fired at 850 °C for 4 hours to obtain a block solid, which is then crushed and sieved through a 120 mesh sieve to obtain a pre-fired powder; (2) The pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol medium for 24 hours, then dried at 80 °C, and sieved through a 120 mesh sieve to obtain a raw material powder; (3) The raw material powder obtained in step (2) is mixed with PVA and rolled to compress into a sheet with a thickness of 30-50 μm, and the amount of PVA added is 42% of the mass of the raw material powder; (4) The sheet with a thickness of 30-50 μm is degreased at 600 °C for 24 hours; (5) After degreasing, the sample is sintered into a ceramic at 1160 °C for 2 hours to obtain a ceramic material with wide temperature stability and high energy storage performance.

[0059] The prepared sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage density is used to test the surface grain growth of the sintered ceramic sample using a field emission scanning electron microscope, and the results are shown in Figure 6 The grain size is reduced to 1.47 μm. The sintered sample is processed into a sheet with smooth two sides and a thickness of about 0.1 mm, gold-plated electrodes are applied, and then the ferroelectric properties thereof are tested at room temperature and a frequency of 10 Hz, and the results are shown inFigure 11 The hysteresis loop of the ceramic material of the present embodiment measured at room temperature is shown. The energy storage density of the energy storage ceramic of the present embodiment at room temperature can reach 10.08 J / cm 3 , and the energy storage efficiency can reach 85 %. The energy storage characteristics of the energy storage ceramic material of the present embodiment at room temperature are shown in Table 1.

[0060] As Figure 21 shown are the hysteresis loop diagrams of the energy storage ceramic material of the present embodiment at 10 Hz frequency and 300 kV / cm electric field intensity at 20 °C, 40 °C, 60 °C, 80 °C, 100 °C, 120 °C and 140 °C, respectively. The energy storage characteristics calculated from the hysteresis loop show that the energy storage density of the energy storage ceramic of the present embodiment at 10 Hz frequency remains between 1.94~1.71 J / cm 3 , and the energy storage efficiency remains between 89.5~90.5 %. As Figure 22 shown are the hysteresis loop diagrams of the energy storage ceramic material of the present embodiment at room temperature and 150 kV / cm electric field intensity at 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz, and 100 Hz frequency, respectively. The energy storage characteristics calculated from the hysteresis loop show that the energy storage density of the energy storage ceramic material of the present embodiment at room temperature and 300 kV / cm electric field intensity remains between 1.97~1.87 J / cm 3 , and the energy storage efficiency remains between 86.96~89.70 %, which indicates that the energy storage performance of the energy storage ceramic material of the present embodiment is high, and exhibits good temperature stability and frequency stability. The energy storage characteristics of the energy storage ceramic material of the present embodiment at room temperature are shown in Table 1. Table 5 shows the energy storage characteristics of the energy storage ceramic material of the present embodiment at 10 Hz frequency and 300 kV / cm electric field intensity at 20 °C, 40 °C, 60 °C, 80 °C, 100 °C, 120 °C and 140 °C, respectively. Table 6 shows the energy storage characteristics of the energy storage ceramic material of the present embodiment at room temperature and 300 kV / cm electric field intensity at 1 Hz, 2 Hz, 5 Hz, 10 Hz, 20 Hz, 50 Hz and 100 Hz frequency, respectively.

[0061] Table 1 Energy storage characteristics of the energy storage ceramic material with wide temperature stability and high energy storage density of the present embodiment at room temperature and 10 Hz

[0062] Table 2 Energy storage characteristics of the energy storage ceramic material with wide temperature stability and high energy storage density of Example 3 at 10 Hz frequency at different temperatures

[0063] Table 3 Energy storage properties of the ceramic material with wide temperature stability and high energy storage density of Example 3 at different frequencies under room temperature conditions

[0064] Table 4 Charge and discharge properties of the ceramic material with wide temperature stability and high energy storage density of Example 3 under room temperature and 200 kV / cm electric field intensity

[0065] Table 5 Energy storage properties of the ceramic material with wide temperature stability and high energy storage density of Example 5 at different temperatures under 10 Hz frequency

[0066] Table 6 Energy storage properties of the ceramic material with wide temperature stability and high energy storage density of Example 5 at different frequencies under room temperature conditions

[0067] As shown in Table 1, with the continuous increase of the doping amount of (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, the remanent polarization of the sodium bismuth titanate-based energy storage ceramic material of the present application gradually decreases, and the breakdown field strength shows a trend of first increasing and then decreasing, and under a certain ratio, higher energy storage density and energy storage efficiency can be obtained, and the energy storage density and efficiency can reach 5.84 J / cm 3 and 85.7 % at room temperature, respectively; as shown in Table 2, the energy storage density of the energy storage ceramic material of Example 3 in the present application can be maintained at 0.756~0.71 J / cm 3 under the conditions of a frequency of 10 Hz and an electric field intensity of 150 kV / cm at 20~140 °C, and the energy storage efficiency fluctuates between 91.87~92.29 %; as shown in Table 3, the energy storage density of the energy storage ceramic material of Example 3 in the present application can be maintained at 0.784~0.72 J / cm 3 under the conditions of room temperature and an electric field intensity of 150 kV / cm at 1~100 Hz, and the energy storage efficiency can be maintained at 90.69~92.22 %, and the energy storage density and the energy storage efficiency do not fluctuate greatly, showing good frequency stability.

[0068] As shown in Table 5, the energy storage density of the energy storage ceramic material of Example 5 in the present application can be maintained at 1.94~1.76 J / cm 3and the energy storage efficiency fluctuates between 89.5~90.5 %; from Table 6, it can be seen that the energy storage density of the energy storage ceramic material of Example 5 in the application can be maintained at 1.97~1.87 J / cm 3 under the conditions of room temperature and an electric field intensity of 300 kV / cm at a frequency of 1~100 Hz

[0069] From Table 4, it can be seen that the current density of the sodium bismuth titanate-based high-energy storage and charge-discharge performance ceramic material of Example 3 can reach 506.9 A / cm 2 under the conditions of room temperature and an electric field intensity of 200 kV / cm 3 The power density can reach 76.03 MW / cm 0.5 The discharge time is as short as 64.1 ns. 0.5 It can be found from the above examples that the doping amount of (Li 0.8 La 0.2 )(Zr 0.5 Ti 0.5 )O3 effectively overcomes the shortcomings of low dielectric breakdown field strength and energy storage density and large dielectric loss of sodium bismuth titanate-based ceramic dielectric materials, the prepared sodium bismuth titanate-based energy storage ceramic dielectric material exhibits excellent energy storage performance and has good temperature and frequency stability, is suitable for a wide working temperature and frequency range and application fields, has a large power density and an ultrafast discharge rate, and is expected to be applied to advanced energy storage systems.

[0070] Example 6 The chemical formula of the sodium bismuth titanate-based ceramic material of this example is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.8 La 0.2 )(Zr 0.5 Ti 0.5 )O3, wherein x represents a mole fraction, and x =0.15. The preparation method of the above sodium bismuth titanate-based ceramic material with wide temperature stability comprises the following steps: (1) according to the chemical formula: 0.85(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)-0.15(Li 0.8 La 0.2)O3, analytical pure Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are dosed, mixed uniformly by ball milling for 24 hours in anhydrous ethanol medium, then dried at 80 °C, sieved through 120 mesh, briquetted, and then pre-fired at 800 °C for 5 hours to obtain a blocky solid, then the blocky solid is crushed and sieved through 120 mesh to obtain a pre-fired powder; (2) the pre-fired powder obtained in step (1) is ball milled in anhydrous ethanol medium for 24 hours, then dried at 80 °C, and sieved through 120 mesh to obtain a raw material powder; (3) the raw material powder obtained in step (2) is cold isostatic pressed, wherein the pressure of the cold isostatic pressing is 180 MPa, and the pressure holding time is 3 minutes; the round sheet obtained after pressure pressing is sintered into porcelain at 1060 °C for 3 hours to obtain the ceramic material with wide temperature stability and high energy storage density.

[0071] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A sodium bismuth titanate-based ceramic material having a wide temperature stability and a high energy storage density, characterized in that, The chemical formula of the bismuth sodium titanate-based ceramic material with wide temperature stability and high energy storage performance is: (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3, wherein 0.05≤ x ≤0.

20.

2. The bismuth sodium titanate-based ceramic material with wide temperature stability and high energy storage density according to claim 1, characterized in that, The sodium bismuth titanate-based ceramic material with wide temperature stability and high energy storage performance has an energy storage density of 3.85-10.08 J / cm 3 at a frequency of 10 Hz, and an energy storage efficiency of 81.2-88 %.

3. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 1 or 2, characterized in that, The method comprises the following steps: (1), according to the stoichiometric ratio of (1- x )(0.85Na 0.5 Bi 0.5 TiO3-0.15CaTiO3)- x (Li 0.5 La 0.5 )(Zr 0.8 Ti 0.2 )O3((1- x ) of the stoichiometric ratio, Na2CO3, Bi2O3, TiO2, CaCO3, La2O3, Li2CO3 and ZrO2 are uniformly mixed to obtain a first raw material powder, and a pre-sintered solid is obtained after pre-sintering; (2) ball-milling and sieving the pre-sintered solid obtained in step (1) to obtain a second raw material powder; (3) pressing the raw material powder obtained in step (2) into a shape and then sintering at a high temperature to obtain a ceramic material with wide temperature stability and high energy storage performance.

4. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 3, characterized by, In step (1), the pre-sintering temperature is 800-850 °C, and the pre-sintering is performed for 3-5 hours.

5. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 3, characterized by, In step (3), the pressing into a shape is performed by using a cold isostatic pressing machine.

6. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 5, characterized by, The cold isostatic pressing pressure is 180-220 MPa, and the time is 3 min.

7. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 3, characterized by, In step (3), the sintering temperature is 1060-1120 °C, and the sintering time is 2-4 hours.

8. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 3, characterized by, The method further comprises step (4), wherein in step (4), the raw material powder obtained in step (2) is mixed with PVA, and then rolled and compressed into a sheet with a thickness of 30-50 μm, and then sintered at a high temperature after degassing to obtain a ceramic material with wide temperature stability and high energy storage performance.

9. The method of producing a bismuth sodium titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 8, characterized by, The degassing temperature is 600 °C, and the degassing time is 24 hours.

10. The method of producing a sodium bismuth titanate-based ceramic material having a wide temperature stability and a high energy storage density according to claim 8, characterized by, The sintering temperature is 1160 °C, and the sintering time is 2 hours.